Regional Power Shifts and Climate Knowledge Systems: South Africa as a Climate Power? - Babette Never (German Institute of Global and Area Studies (GIGA), 2010)
In the international system, there has been a power shift towards regional powers, which can be illustrated by recent developments in climate governance. I argue that some of these regional powers are also climate powers, which benefit from an issue-specific power shift. The behavior and strategies of those climate powers are central for global climate governance. To analyze their strategies, a multi-level approach is required that captures the link between domestic climate governance and climate foreign policy. I develop such a concept of climate knowledge systems. It is based on Emanuel Adler's theory of cognitive evolution and communities of practice. A pragmatist philosophy such as this that allows for mixed methods research is most suitable for analyzing the proposed connection between knowledge, practices and change. It also presents the key to an extended regional powers framework, leaving the somewhat artificial boundaries of international relations in climate governance behind. The concept of climate knowledge systems is empirically applied to South Africa with some early tentative results of an online expert survey, as well as the analysis of data of the Carbon Disclosure Project. – – Im Internationalen System findet eine Machtverschiebung zugunsten der regionalen Führungsmächte statt, die in den jüngeren Entwicklungen im Klima-Governance-Feld deutlich wird. Einige der regionalen Führungsmächte sind auch Klimamächte, die von einer policy-spezifischen Machtverschiebung profitieren. Das Verhalten und die Strategien regionaler Führungsmächte in Bezug auf den Klimawandel sind zentral für die globale Klima-Governance. Für die Analyse der Strategien ist ein Multi-Level-Ansatz notwendig, der die Verbindung zwischen nationaler Klima-Governance und Klima-Außenpolitik erfasst. Ich entwickle ein solches Konzept der Klima-Wissenssysteme. Es basiert auf Emanuel Adlers Theorie der kognitiven Evolution und Communities of Practice. Ein philosophischer Ansatz im Sinne des Pragmatismus, der den Einsatz von qualitativen und quantitativen Methoden ermöglicht, ist am besten für die Analyse der Verbindung von Wissen, Praktiken und Wandel geeignet. Er bildet ferner den Schlüssel zu einem erweiterten Analyserahmen für regionale Führungsmächte, in dem die teils künstlichen Grenzen der Internationalen Beziehungen im Klima-Governance-Feld hinter sich gelassen werden. Das Konzept der Klima-Wissenssysteme wird ferner empirisch auf Südafrika angewandt. Ich lege erste vorläufige Ergebnisse aus einer Online-Experten-Umfrage und den Daten des Carbon Disclosure Project vor.
Keywords: 300; South Africa; regional powers; climate governance; communities of practice; knowledge systems; mixed methods; Klimaschutz; Governance-Ansatz; Geopolitik; Südafrika